Open Access & Open Data In Accordance With The Fair And Care Principles - Havemann, Jo (My University, 2023)
Workshop held at the UbuntuNet Connect Conference 2023 for librarians in Kampala, Uganda.
Keywords: Open Access; Open Science; Meta Data